Acetyl-L-carnitine in painful peripheral neuropathy: a systematic review - Di Stefano G (Journal of Pain Research, 2019)
Giulia Di Stefano, Andrea Di Lionardo, Eleonora Galosi, Andrea Truini, Giorgio CruccuDepartment of Human Neuroscience, Sapienza University, Rome, ItalyAbstract: Acetyl-L-carnitine (ALC) has shown a neuroprotective effect in patients with peripheral neuropathies of different etiologies. Preclinical studies demonstrated a central anti-nociceptive action, both in neuropathic and nociceptive pain models. The present review aims to provide the knowledge on the efficacy of ALC in patients with painful peripheral neuropathy, based on the evidence. Consistent with the PRISMA statement, authors searched PubMed, Embase and the Cochrane Database of Systematic Reviews for relevant papers, including those issued before April 2018. Two authors independently selected studies for inclusion and data extraction: only trials including patients with a diagnosis of peripheral neuropathy and involving at least 10 patients were considered for the purposes of this review. Fourteen clinical trials were revised, to provide the level of evidence for neuropathy. To assess the global efficacy of ALC in painful peripheral neuropathy, a meta-analysis of four randomized controlled trials was performed. Mean difference in pain reduction as measured on a 10-cm VAS, and 95% CIs were used for pooling continuous data from each trial. Four randomized controlled trials tested ALC in patients with neuropathy secondary to diabetes and to antiretroviral therapy for HIV. Compared to placebo, ALC produced a significant pain reduction equal to 20.2% (95% CI: 8.3%-32.1%, P<0.0001) with respect to baseline. Clinical trials also showed beneficial effects on nerve conduction parameters and nerve fiber regeneration, with a good safety profile. These data indicate that ALC provides an effective and safe treatment in patients with painful peripheral neuropathy. We recommend further studies to assess the optimal dose and duration of the therapeutic effect (also after treatment withdrawal).Keywords: neuropathic pain, treatment, neuroprotective function, epigenetic mechanism